Leading with Heart: Urban Elementary Principals as Advocates for Students - Mariela A. Rodríguez; Elizabeth Murakami-Ramalho; William G. Ruff (Educational Considerations, 2009)
Principals in urban settings serve elementary schools often densely populated with highly mobile, ethnically diverse, and economically disadvantaged students.
Keywords: Principals; urban elementary; role; advocates; school; administrators; secondary; accountability; leadership; conceptual; methodology; students